Synthesis, Characterization and Biological Activities of New Schiff Base Compound and Its Lanthanide Complexes - Abdel-Az; Maisa Siddiq Abduh; Sultan Ayesh Mohammed Saghir; Naif Al-Gabri (MDPI AG, 2022)
The thermal condensation of 3-(2-Furyl)acrolein with 2-Amino-6-ethoxybenzothiazole generated a new Schiff base, (1E,2E)-N-(6-ethoxybenzo[d]thiazol-2-yl)-3-(furan-2-yl)prop-2-en-1-imine (L), with general formula of C16H14N2O2S. Also, a series of lanthanide complexes of gadolinium, samarium, and neodymium (La-Lc) were synthesized utilizing acetonitrile as the solvent and triethylamine as a buffer and catalyst. Based on elemental analysis, mass spectroscopy, and FTIR analysis, all of the Bis-(1E,2E)-N-(6-ethoxybenzo[d]thiazol-2-yl)-3-(furan-2-yl)prop-2-en-1-iminetri-nitratolanthanide(III) complexes with the general formula [LnL2(NO3)3]·H2O are solids with a 2:1 molar ratio (ligand: metal). Based on conductivity estimates, they are nonelectrolytes and monoatomic paramagnetic according to the magnetic moment measurements, and one mole of lattice water was found after thermal gravimetric measurements and FTIR analysis. Therefore, the lanthanide complexes show a ten-coordination structure with a deformed bicapped square antiprismatic. The Schiff base and its complexes were screened for their antimicrobial, antifungal, antioxidant, and antitumor properties. Their antimicrobial and antifungal activities were strong, and they also produced good antioxidant and antitumor effects.